Pengaruh penawaran diskon dan kemudahan pembayaran terhadap peningkatan penjualan e-commerce - Nafis, M. Azie Azizman; Fahriani, Dian; Wicaksono, Achmad; Anwar, Chairil (Jurnal Akuntansi dan Manajemen, 2025)
This study aims to examine the influence of discount offers and payment convenience on consumer behavior to increase e-commerce sales at SRC Woro Beringin Kembar in Sepande Village. The research focuses on how marketing strategies affect purchasing decisions within the context of small-scale e-commerce operations. The study population consisted of 328 consumers, with a sample of 80 respondents determined using the Slovin formula. Data were collected through structured questionnaires and analyzed using SPSS version 21. The results indicate that both discount offers and payment convenience have a positive and significant effect both partially and simultaneously on consumer purchasing decisions. These findings suggest that implementing appropriate discount strategies and enhancing payment flexibility are effective approaches to stimulate consumer interest and drive sales growth. This study provides practical insights for micro and small e-commerce businesses in optimizing marketing strategies aligned with consumer preferences.